(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
Relevance. This article explores the pressing issue of inclusive education in the context of physical education for children with disabilities, with a particular focus on the implementation of adaptive badminton as a means of physical rehabilitation, social integration, and personal development. Adaptive badminton is presented as an effective fitness technology that enables children with musculoskeletal, visual, auditory, and other impairments to actively participate in physical education, promoting the development of motor skills, enhancing functional capabilities, and fostering motivation for self-realization. The purpose of the study. To study the status and possibilities of using adaptive badminton (parabadminton) in the process of physical education of children with disabilities. Research methods. The study used general scientific methods: analysis, synthesis, generalization, classification of facts of scientific literature, questionnaires, methods of mathematical statistics. Based on a survey of physical education teachers from various regions of Ukraine, the study analyzes the accessibility of sports infrastructure, the availability of adaptive tools for students with disabilities, and teachers’ awareness of the specific requirements for organizing inclusive physical education. The findings reveal that only one-third of respondents conduct classes with children with disabilities, and over 70% of educational institutions lack adequate conditions for implementing inclusive physical education. Special attention is given to the possibilities of adaptive badminton for different categories of students, including those who use wheelchairs, crutches, or have short stature. Within the framework of the social protection system for people with disabilities, measures aimed at physical rehabilitation and social adaptation demonstrate particular effectiveness. One of such means is adaptive badminton, which in the context of inclusive education acts not only as a form of physical activity, but also as a tool for personality development, integration into the social environment and the formation of vital competencies.